Transforming Islamic Religious Education Learning through 21st-Century Skills: A Systematic Literature Review - Muhamad Basyrul Muvid; Alaika Muhamad Bagus Kurnia; Firmansyah Firmansyah; Nanang Lidwan (AL-ISHLAH: Jurnal Pendidikan, 2026)
The transformation of Islamic Religious Education (PAI) has become increasingly important in responding to the demands of 21st-century education, which requires learners to develop critical thinking, creativity, communication, collaboration, and strong moral character. Although previous studies have examined pedagogical innovation, digital technology integration, and character education in PAI, the existing literature remains fragmented, with limited integrative synthesis of these dimensions within Islamic educational contexts. This study aims to synthesize current evidence on the transformation of PAI and develop an integrative conceptual framework that supports the development of 21st-century competencies. A Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines was conducted. Following the identification, screening, eligibility, and inclusion process, 25 peer-reviewed articles published between 2020 and 2025 were selected for qualitative synthesis. The review demonstrates that effective PAI transformation is achieved through the integration of three interrelated dimensions: pedagogical innovation, digital technology, and character education grounded in Islamic values. Rather than functioning independently, these dimensions interact synergistically to create adaptive, student-centered, and contextually relevant learning environments that foster both academic competence and religious character while strengthening students' 21st-century skills. This study contributes by proposing an integrative conceptual framework for PAI transformation aligned with 21st-century competencies. The framework provides a comprehensive synthesis that bridges pedagogy, technology, and Islamic character education, offering theoretical insights and practical guidance for curriculum development and instructional practice in contemporary Islamic education.